Use of milk progesterone and PGF2α in a scheduled insemination program - Jeffrey S. Stevenson; J. R. Pursley (Kansas Agricultural Experiment Station Research Reports, 1993)
Holstein cows milked twice daily were assigned to be inseminated at their first detected estrus (control) after 42 days in milk or received PGFza (PG) after 42 days, if they had a high milk progesterone (P4) test on any of 3 consecutive Mondays until first inseminated. Milk P4 tests and injections of PG were given on Mondays, and most of the breeding occurred on Thursdays and Fridays. The proportion of cows inseminated within 21 days of the beginning of the breeding period was greater in the milk P4 + PG group (52.8%) than in the control (38.9%). Compared to controls, use of PG reduced days to first service by 12.2 ± 3.1 d, calving intervals by 23.3 ± 8.9 d, rate of reproductive culling, and cost per pregnancy. We concluded that using PG as a management tool in an AI program is warranted and cost effective. However, the milk P4 test would not be justifiable unless its cost were significantly lower than the cost of a weekly injection of PG.; Dairy Day, 1993, Kansas State University, Manhattan, KS, 1993;
Keywords: Dairy Day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-149-S; Report of progress (Kansas Agricultural Experiment Station); 694; PGF2α; Progesterone; A.I.